2015: Which new directions for Alzheimer's disease? - Ludovic Martin (Frontiers Research Topics, 2015)
According to the World Health Organization, more than 40 million people in the world are affected with dementia. To date, 60-70% of the cases of dementia are attributed to the Alzheimer's disease (AD). This neurodegenerative disorder gradually takes place over a period of at least 20 years before the onset of symptoms, which are impaired memory, apathy and depression. The characteristics of AD consist in neurofibrillary tangles (intraneuronal aggregates of hyperphosphorylated tau proteins) and senile plaques (dense extraneuronal deposits composed of amyloid ß (Aß)). The other features linked to these two core pathological hallmarks of AD are inflammation, oxidative stress, progressive synaptic and neuronal loss. In past years, some of the emerging therapeutic strategies against AD were employed to deal with the pathological hallmarks of the disease. Science teams all over the world try to restore the tau phosphorylation equilibrium. Their purpose is to interfere with the aggregation of tau and decrease its amount of proteins per se as well. Furthermore, they are trying either to stimulate the elimination processes of the aggregated tau proteins or to stop the formation of Aß peptides. This could be reached by the stimulation of the classic techniques of protein degradation such as the autophagic pathway, or by the targeted immunotherapy. In this Research Topic, we wish to summarize and review the etiology of AD and the related therapeutic opportunities for the next decades. To fully understand the precise mechanisms underlying AD, research findings, reviews, new insights and new approaches include AD and related tauopathies, tau phosphorylation balance, pharmacological compounds against AD, neuroprotection strategies and new therapeutic ways but also risk factors for AD and AD genetic information are included in this issue.